2016
DOI: 10.1352/1944-7558-121.6.501
|View full text |Cite
|
Sign up to set email alerts
|

Using the Teaching Interactions Procedure to Teach Social Skills to Children With Autism and Intellectual Disability

Abstract: This study implemented a modified teaching interaction procedure to teach social skills to 4 children diagnosed with autism spectrum disorder with an intellectual disability. A multiple baseline design across social skills and replicated across participants was utilized to evaluate the effects of the modified teaching interaction procedure. The results demonstrated that the teaching interaction procedure resulted in all participants acquiring targeted social skills, maintaining the targeted social skills, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…B. Leaf, Townley-Cochran et al, 2016e;Libby et al, 2008;Luyben et al, 1986;Ng et al, 2016;Seaver & Bourret, 2014;Soluaga et al, 2008;Wolery et al, 1990). Therefore, it is not surprising that each of the prompting strategies were also effective in the current investigation, with minimal differences across the three conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…B. Leaf, Townley-Cochran et al, 2016e;Libby et al, 2008;Luyben et al, 1986;Ng et al, 2016;Seaver & Bourret, 2014;Soluaga et al, 2008;Wolery et al, 1990). Therefore, it is not surprising that each of the prompting strategies were also effective in the current investigation, with minimal differences across the three conditions.…”
Section: Discussionmentioning
confidence: 99%
“…B. Leaf, Taubman, McEachin, Leaf, & Tsuji, 2011;Ng, Schulze, Rudrud, & Leaf, 2016;Soluaga et al, 2008).…”
mentioning
confidence: 99%
“…The results, which were similar to those of Leaf et al (2012), showed that participants reached the mastery criterion only for the skill taught with the teaching interaction procedure. Ng, Schulze, Rudrud, and Leaf (2016) expanded the implementation of the teaching interaction procedure for individuals diagnosed with ASD who were more impacted (e.g., limited vocal-verbal repertoires, had high rates of stereotypic behavior, and demonstrated fewer social behaviors). In this study, the authors modified the teaching interaction procedure by incorporating visuals (e.g., pictures of the rationales).…”
mentioning
confidence: 99%
“…Em casos de ensino de comportamentos sociais, teste de generalização, validade social e follow up são essenciais, já que comportamentos sociais são modelados e mantidos pela comunidade verbal (Skinner, 1981). Seis estudos (Artigos 1, 2, 3, 4, 5 e 8) avaliaram generalização, sete ( Artigos 1,4,5,6,7,9 e,11) verificaram a manutenção dos comportamentos por meio de uma fase de follow up e apenas três (Artigos 1, 6, 10) avaliaram a validade social do trabalho desenvolvido. A ausência de generalização, follow up e validade social em grande parte dos estudos e a ausência de um termo ou unidade de medida padronizada para avaliar o ensino do empatizar impactam na confiabilidade dos resultados.…”
Section: Discussionunclassified